PERAN KEPEMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN BUDAYA RELIGIUS DI SMP N 2 BATANG PERANAP KABUPATEN INDRAFIRI HULU - Nova Ayu Wulandari; Andrizal Andrizal; Ikrima Mailani (Universitas Islam Kuantan Singingi, 2020)
The succesof an educational institution depends very much on theleadership of the principal. School success is that good principals behavedynamically to prepare various education progrsms. Even the high and lowquality of a school is distinguished by the leadership of the school principal. Thecreation of an atmosphere or religious culture means creating an atmosphere orclimate of religious life. In the sense of the word creation of the religiousatmosphere is carried out with practice, invitations (persuasive) and habituation of religious attitudes both vertically (hablumminallah) and horizontalally (hablumminannas) I in the school environtment. This type of research used in this study is field research that is descriptive qualitative. Concerning the role ofthe principal’s leadership in developing religious culture in SMP N 2 Batang Peranap, Indragiri Hulu district. Data obtained through observation,interviewsand documentation.The leadership role of the headmaster in implementing religious culture inSMP N 2 batang the role of Indragiri upstream district plays a good role, becausethe school principal in SMP N 2 batang peranap kabupaten Indragiri huludistrictas a whole is able to direct, pay attention, apply, religious culture toteachers, students, and school residents. But hus weaknesses, because theheadmaster is muslim and even in the school does not have non muslim teachers.Thus the religious teacher cannot explore what religious activities and habits will be applied to non-muslim students. Factors that renew the leadership role of the principal indeveloping religious culture in SMP N 2 batang peranap the role of Indragiri hulu regency can be concluded, namely internal factors originating from oneself, authority and habits of the school principal. And external factors which come from teachers, students, the school environment, the community, the situation and conditions of the area.